MECHANISM FOR IMPLEMENTING AN INNOVATIVE DEVELOPMENT STRATEGY IN TEXTILE ENTERPRISES (International Congress on Economics, Management and Business Studies, 2026)
This article examines the mechanism for implementing an innovative development strategy in textile enterprises. A conceptual model for developing and implementing a strategy aimed at fostering innovative activity within enterprises is substantiated.
Keywords: innovation process, ensure the efficient use of available resources